PERAN KEPALA DESA DALAM MENGELOLA PEMBANGUNAN DI DESA MAHATO KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU PROPINSI RIAU - Armansyah Armansyah; Yuritanto Yuritanto (Sekolah Tinggi Pariwisata Mataram, 2022)
One of the success of village development is very, by the role of a Village Head, thus the role of a Village Head is very important and very necessary in the village development process in order to facilitate development and increase community awareness to participate in village development, one of the villages is the Village Mahato, Tambusai Utara District, based on the results of observations and preliminary surveys by researchers of the phenomena that: first, there is a village development concept / model that can be an optimal solution in efforts to alleviate poverty and increase agricultural and plantation products for the people of Mahato Village, second, implemented village development in a sustainable manner because it has a very clear concept and this will guarantee a sustainable development. third, human resources in the village, both the apparatus and the community, make a major contribution to the implementation of village development itself, this is obtained because of the awareness of local entrepreneurs to be involved in the development of Mahato village, and other resources such as the Regency and Provincial APBD and APBN through Village funds. The type of research used is descriptive qualitative research. The details of the informants used in this research are as follows: 1 person Village Head, 1 Village Secretary and 6 Village Officials, 4 Hamlet Head, The role of the village head as a mobilizer, namely the village head to mobilize or invite the community to jointly take concrete actions to develop the village. In increasing public awareness to participate in every activity, there are various ways that the Village takes in inviting the community in every activity, this is done to facilitate the implementation of development in the Village and so that the Mahato Village residents are accustomed to positive planned village activities.